Occurrence of the alien sea hare Aplysia dactylomela Rang, 1828 (Opisthobranchia, Aplysiidae) in Malta - SCHEMBRI, P.J. (Mediterranean Marine Science, 2008)
The alien sea hare Aplysia dactylomela, which is already established in several localities in the central and eastern Mediterranean, is recorded for the first time from Malta on the basis of a specimen photographed at Cirkewwa (northern Malta). It is hypothesised that the occurrence of this species in Malta is a recent event and may be due to range expansion of the species.